Bio-inspired chitosan/polyvinyl alcohol/tannic acid hydrogels as plant grafting wood adhesives - Haejin Bae; Hyun Ho Shin; Ji Hyun Ryu (APL Materials)
Recently, there has been growing interest in plant-inspired materials for various biological, medical, and industrial applications. Notably, tannic acid-based materials exhibit remarkable adhesive properties and can be used in a variety of applications, particularly biomedical applications. In addition, mixtures composed of tannic acid and polymers (e.g., polyvinyl alcohol) exhibit excellent adhesion to various substrates. In this study, we developed gallol-containing chitosan (G-CS), polyvinyl alcohol (PVA), and tannic acid (TA) composite (G-CPT) hydrogels as wood adhesive materials. G-CPT hydrogels were immediately formed by mixing the G-CS/PVA solution with the TA solution. Rheological analysis revealed an increase in the elastic modulus (G′) with the addition of small amounts of G-CS. In addition, the detachment stress of wood sticks attached using G-CPT hydrogels was 142.2 ± 7.2 MPa, which was substantially higher than that of G-CS (5.3 ± 1.4 kPa), PVA (2.2 ± 0.2 kPa), TA (0.4 ± 0.1 kPa), and PVA/TA hydrogels (106.5 ± 2.5 MPa). Furthermore, G-CPT hydrogels can be used as wood adhesives for scion grafting into the rootstock of English ivy. These findings highlight the importance of G-CPT hydrogels as eco-friendly wood adhesives with enormous potential for various industrial and agricultural applications.